Beispiel Nr: 14
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ 4x^3+5x^2-6x =0\\ \\ \textbf{Rechnung:} \\ x( 4x^2+5x-6)=0 \Rightarrow x=0 \quad \vee \quad 4x^2+5x-6=0\\ \\ 4x^{2}+5x-6 =0 \\ x_{1/2}=\displaystyle\frac{-5 \pm\sqrt{5^{2}-4\cdot 4 \cdot \left(-6\right)}}{2\cdot4} \\ x_{1/2}=\displaystyle \frac{-5 \pm\sqrt{121}}{8} \\ x_{1/2}=\displaystyle \frac{-5 \pm11}{8} \\ x_{1}=\displaystyle \frac{-5 +11}{8} \qquad x_{2}=\displaystyle \frac{-5 -11}{8} \\ x_{1}=\frac{3}{4} \qquad x_{2}=-2 \\ \underline{x_1=-2; \quad1\text{-fache Nullstelle}} \\\underline{x_2=0; \quad1\text{-fache Nullstelle}} \\\underline{x_3=\frac{3}{4}; \quad1\text{-fache Nullstelle}} \\$